Dealing with the diversity of interoperability types - Santos, Kécia Souza Santana; Valle, Pedro Henrique Dias; Maciel, Rita Suzana Pitangueira (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Context: Interoperability is a crucial non-functional requirement for current information systems since systems can collaborate, exchange information, and use the information that has been shared. Interoperability has many types, such as semantic, legal, cultural, and organizational. Several interoperability types arose to characterize distinct information systems collaboration heterogeneity and barriers. Problem: However, various interoperability types do not have a common shared definition, leading to ambiguity and hampering developers from having a comprehensive view of the interoperability requirements they hope to achieve. Solution: We propose a conceptual model to describe and classify interoperability types reported in the scientific literature. This model aims to support developers in identifying interoperability types required in a given collaboration among information systems. IS Theory: We followed the design theory regarding the artifacts that contribute to the construction of IS. Method: The conceptual model was specified based on evidence collected from the scientific literature. It comprises two diagrams that describe and classify the interoperability types. We conducted a exploratory study with 33 information systems developers to validate our proposed conceptual model. Summary of Results: The conceptual model achieved 87.9% acceptance for the classification diagram, while the description diagram had 78.8% acceptance. Contributions and Impact in the IS area: This research work may help to comprehend how developers understand and use interoperability requirement specifications that require a particular solution to be fulfilled in an information system. In addition, this work also aims to contribute to the Full Interoperability and Systems-of-Systems Interoperability (SOSI) challenges proposed in I GrandSI-BR: 2016-2026.